The associations among meaningfulness, leisure activity and cognitive functioning in adulthood - Hatt, Cassandra Rae, author; Bielak, Allison, advisor; Eakman, Aaron, committee member; Diehl, Manfred, committee member; Luong, Gloria, committee member (Colorado State University. Libraries, 2022)
There is considerable research that has shown that individuals who engage in more social, physical, and cognitive leisure activities have higher cognitive ability and performance across older adulthood (Bielak et al., 2012; Hertzog et al., 2008). However, some studies have failed to report significant associations between leisure activity engagement and cognitive functioning (Hambrick et al., 1999; Parisi, 2010). Differences in findings in the activity literature have been discussed as resulting from differences in methodological designs and inconsistency in the measurement of constructs (Bielak, 2010; Bielak & Gow, 2022). One important area of interest involves research on the psychological and contextual modifiers that influence the activity-cognition relationship. This dissertation examined the relationships between activity engagement, meaningfulness and cognition using both cross-sectional (Study 1) and longitudinal (Study 2) research designs. Eighty-one individuals aged 45- 90 years old (Mage = 61.26 years, SD = 12.18) who participated in the Recording Everyday Activities and Cognition using Tablets (REACT) study at Colorado State University were used for analysis. In Study 1, exploratory and confirmatory factor analysis was performed on each latent construct using the following baseline assessments: Victoria Longitudinal Study Activity Questionnaire (VLS-AQ); Engagement in Meaningful Activities Survey (EMAS); and seven standardized cognitive tasks administered using paper/pencil and computerized formats. Mediation analysis was then performed using structural equation modeling to test multiple mediation pathways linking baseline activity and meaningfulness to cognition. The results revealed a significant direct effect of meaningfulness on activity but failed to associate either meaningfulness or activity with cognitive performance at baseline. In the short-term longitudinal analysis (Study 2), day-to-day fluctuations in activity and meaningfulness were examined using a form of ecological momentary assessment across 14-days of tablet testing. Multilevel modeling analysis allowed for within and between-person level effects to be tested in models predicting performance across three cognitive tasks (Symbol Search Task (SST), Location Dot Memory (LDM), Flip-Back Task (FBT). Study 2 results showed significant between and within-person effects of daily meaningfulness and daily activity on cognition, particularly for the SST, a measure of visual-processing speed, and for LDM, a measure of working memory. Contrary to hypothetical predictions however, the direction of the between effects were unanticipated. For meaningfulness factor 2 (MF2) and activity, negative between-person effects and positive within-person effects emerged, although for meaningfulness factor 1 (MF1) positive between-person effects were significant, but the within-person effects were nonsignificant. Similar trends emerged for LDM; there were significant negative between-person and significant positive within-person effects for MF2 and activity, but no significant effects were found for FBT performance. Unexpected within-person level effects demonstrated that associations between meaningfulness, activity and cognition functioned differently at the group (i.e., between-person level) than at the individual (i.e., within-person level). Demonstrating that on days when individuals engaged more frequently in socially meaningful activities, or had higher daily activity levels, there was a counterintuitive effect on same-day cognition. Consideration of the psychological context of engagement is a crucial aspect in understanding the activity-cognition relationship, however further investigation of the social, physical, and cognitive aspects of the everyday environment that promote cognitive health is warranted. Although no cross-sectional support for the activity-cognition relationship was gained through Study 1, the findings revealed that subjective meaning for activity-related experiences is an important precursor associated with the selection and evaluation of leisure activity engagement. At the daily level, Study 2 showed support for the activity-cognition relationship, showing that fluctuations in daily activity and meaningfulness predicted cognitive performance at both the within and between-person level. The implications for prevention research could aid in development of personalized lifestyle and behavioral management programs that target daily lifestyle and promote engagement in personally meaningful leisure activities.
Keywords: cognitive health; successful aging; meaningfulness; activity engagement